Reactogenicity and immunogenicity of BNT162b2 or mRNA-1273 COVID-19 booster vaccinations after two doses of BNT162b2 among healthcare workers in Japan: a prospective observational study. (2nd September 2022) - Naito, Toshio; Tsuchida, Nao; Kusunoki, Susumu; Kaneko, Yoshihiro; Tobita, Morikuni; Hori, Satoshi; Ito, Suminobu
ABSTRACT: Background: This study evaluates the immunogenicity and reactogenicity of BNT162b2 and mRNA-1273 booster doses after the primary two-dose BNT162b2 series in Japan and is the first report from Western Pacific region. Research design and Methods: Healthcare workers receiving the two-dose BNT162b2 series and eligible for booster vaccination were enrolled. Self-reported adverse reactions were recorded for 8 days. Antibody titer was measured at baseline and on day 28. Results: A total of 2, 931 and 890 subjects received BNT162b2 (homologous) and mRNA-1273 (heterologous) booster vaccinations, respectively. The anti-SARS-CoV-2 spike protein IgG titer increased by 50.9- and 64.3-fold in the homologous and heterologous groups, respectively. Immunogenicity was greater with increasing age, regardless of sex. Adverse reactions were mild to moderate and decreased with age. The most common adverse reactions were injection-site pain (92.2%), fatigue (71.8%), headache (58.3%), and fever ≥37.5°C (46.5%). Two cases of non-severe myocarditis occurred in the heterologous group and resolved without clinical sequelae. Conclusion: Homologous booster schedules had fewer reported adverse reactions; heterologous boosters elicited greater immunogenicity. Among different age groups, subjects aged 60 or over had the lowest immunogenicity before the booster, and both homologous and heterologous boosters restored vaccine immunogenicity level comparable to those of younger age groups.